Understanding the hospitality consumer - Williams, Alistair (Butterworth-Heinemann, 2015)
Presents a different perspective on consumer behaviour in the hospitality sector. This book introduces and explores the role of consumer behaviour theory in the context of hospitality management. It discusses the principles and research of consumer behaviour and illustrates how they are used in the hospitality industry.